A method for preparing carbon-supported Pt-Au bimetallic nanocatalyst
By preparing carbon-supported Pt-Au bimetallic nanocatalysts, the problems of catalyst stacking and low spatial contact surface are solved, and the overall catalytic efficiency of the fuel cell and the utilization rate of precious metals are improved.
Patent Information
- Application Number
- CN202310751602.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-06-25
AI Technical Summary
The superposition and low spatial contact surface of the catalyst lead to low overall catalytic efficiency of the fuel cell, and the accumulation of catalysts is prone to waste of precious metals.
Using the preparation method of carbon-supported Pt-Au bimetallic nanocatalyst, through the preparation of carbon black carrier and the formation of catalytic carrier, the spatial extension and distribution uniformity of the catalyst are improved, thereby improving the catalytic efficiency.
It improves the overall catalytic efficiency of the fuel cell, reduces the waste of precious metals, enhances the spatial contact surface of the catalyst, and improves the distribution of the catalyst.
Smart Images

Figure BDA0004301359860000061 
Figure BDA0004301359860000062 
Figure BDA0004301359860000063
Abstract
Description
Technical Field
[0001] The present invention relates to the field of fuel cells, and in particular to a method for preparing a carbon-supported Pt-Au bimetallic nanocatalyst. Background Art
[0002] Proton exchange membrane fuel cell, abbreviated as PEMFC, is the fifth generation fuel cell. It has the advantages of high power density, high energy utilization, low operating temperature and short start-up time. It is a fuel cell that is easy to miniaturize and modularize. The working principle of PEMFC is that the fuel and oxidant are transported from the flow channels on the anode and cathode bipolar plates respectively, through the diffusion layer to the catalytic reaction layer containing the catalyst, and are ionized into electrons and protons in the anode catalytic layer. The ionized protons will pass through the proton exchange membrane in the battery and be transmitted to the cathode, and the electrons will be transmitted from the anode to the cathode of the PEMFC through the external circuit.
[0003] Catalysts play a key role in the operation of fuel cells. The catalytic efficiency of the catalyst affects the overall effect of the fuel cell, and the distribution of the catalyst has a greater impact on the catalytic effect. Due to the superposition of catalysts and the low spatial contact area, the overall catalytic efficiency of the fuel is not high. At the same time, the accumulation of catalysts can easily cause waste of precious metals during use.
[0004] In summary, after extensive searching by the applicant, it is found that there is at least a problem in this field of catalyst superposition and low spatial contact surface, which leads to low overall catalytic efficiency of fuel cells. Therefore, it is necessary to develop or improve a method for preparing a carbon-supported Pt-Au bimetallic nanocatalyst. Summary of the invention
[0005] Based on this, in order to solve the problem that the superposition of catalysts and the low spatial contact surface lead to the low overall catalytic efficiency of the fuel cell, the present invention provides a method for preparing a carbon-supported Pt-Au bimetallic nanocatalyst, and the specific technical scheme is as follows:
[0006] A method for preparing a carbon-supported Pt-Au bimetallic nanocatalyst, comprising the following preparation method:
[0007] Prepare a carbon black carrier; disperse the carbon black in a mixed solution formed by ethanol and deionized water for 10-15 minutes; after the dispersion is completed, add ethyl orthosilicate dropwise for 30-35 minutes, and continue to disperse for 10-15 minutes after the addition is completed; add epoxy soybean oil and γ-aminopropyl triethoxysilane in sequence and disperse to form a premix, the premix dispersion time is 5-10 minutes, and after the dispersion is completed, dry the mixture to obtain a carbon black carrier;
[0008] Prepare a catalytic carrier; disperse a carbon black carrier and graphene oxide in a mixed solution formed by ethylene glycol and deionized water, and perform ultrasonic dispersion for 5-10 minutes; add acetic acid and γ-(2,3-epoxypropoxy)propyltrimethoxysilane and disperse for 15-20 minutes; after dispersion, add a hydrazine hydrate solution for mixing and dispersion, and adjust the pH to 8-9, and after mixing and dispersion, wash and dry to obtain a catalytic carrier;
[0009] Loading catalyst; the catalytic carrier is dispersed in a mixed solution of chloroplatinic acid solution and chloroauric acid solution, a surfactant is added in the dispersed state, and the dispersion time is 25min-30min; filtering treatment is performed after dispersion, and reduction treatment is performed after filtration to obtain a carbon-loaded Pt-Au bimetallic nanocatalyst.
[0010] Furthermore, in the step of preparing the carbon black carrier, the following addition amounts are included, calculated by weight: 20-24 parts of carbon black, 38-42 parts of ethanol, 18-22 parts of deionized water, 8-12 parts of tetraethyl orthosilicate, 4-6 parts of epoxy soybean oil, and 2-4 parts of γ-aminopropyltriethoxysilane.
[0011] Furthermore, in the preparation of the catalyst carrier, the following addition amounts are included, calculated by weight: 26-30 parts of carbon black carrier, 4-6 parts of graphene oxide, 28-32 parts of ethylene glycol, 4-6 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 22-26 parts of deionized water, 2-3 parts of acetic acid, and 4-6 parts of hydrazine hydrate solution.
[0012] Furthermore, in the catalyst loading step, the following addition amounts are included, calculated by weight: 28-32 parts of chloroplatinic acid solution, 28-32 parts of chloroauric acid solution, 4-6 parts of surfactant, and 33-37 parts of catalytic carrier.
[0013] Furthermore, the carbon black is pre-treated by pickling and oxidation. The pickling is specifically dispersed in a 2mol / L hydrochloric acid solution, with an addition amount of 150g-200g of carbon black per liter of hydrochloric acid solution, and the dispersion time is 40min-50min. After the dispersion is completed, the carbon black is filtered and washed with water until the pH of the filtrate reaches 6-7 and then dried to obtain the pickled carbon black. The oxidation treatment is specifically ultrasonically dispersed in 1L of hydrogen peroxide solution with 20g-25g of the pickled carbon black for 5min-10min, and then transferred to magnetic dispersion for 50min-60min. After the dispersion is completed, the carbon black is filtered and dried.
[0014] Furthermore, the drying process is specifically performed at 60° C.-70° C. for 20 min-30 min.
[0015] Furthermore, the hydrazine hydrate solution is specifically a hydrazine hydrate solution with a mass fraction of 80%.
[0016] Furthermore, the water washing and drying treatment is specifically to use deionized water to wash for 1 min-2 min and then dry at 60° C.-70° C. for 30 min-40 min.
[0017] Furthermore, the chloroplatinic acid solution is specifically a chloroplatinic acid solution with a mass fraction of 1%; the chloroauric acid solution is a chloroauric acid solution with a mass fraction of 1%.
[0018] Furthermore, the reduction treatment is specifically carried out by reducing with hydrogen, and hydrogen is introduced at 110° C.-140° C. for reduction.
[0019] In the above technical scheme, ethyl orthosilicate is added to carbon black so that the surface of the carbon black is coated with silica, and at the same time, the surface is modified by epoxy soybean oil and γ-aminopropyltriethoxysilane so that the surface of the carbon black has silica, epoxy soybean oil and amino groups to form a carbon black carrier; the carbon black carrier and graphene oxide are dispersed and mixed, and the two are distributed more evenly by γ-(2,3-epoxypropoxy)propyltrimethoxysilane to form a catalytic carrier on the surface of the graphene oxide to load the carbon black carrier, wherein the surface of the carbon black carrier is modified so that the entire catalytic carrier has a wide spatial extension, and Pt and Au can be loaded in different spatial directions, thereby improving the overall catalytic efficiency. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0022] A method for preparing a carbon-supported Pt-Au bimetallic nanocatalyst, comprising the following preparation method:
[0023] Prepare a carbon black carrier; disperse the carbon black in a mixed solution formed by ethanol and deionized water for 10-15 minutes; after the dispersion is completed, add ethyl orthosilicate dropwise for 30-35 minutes, and continue to disperse for 10-15 minutes after the addition is completed; add epoxy soybean oil and γ-aminopropyl triethoxysilane in sequence and disperse to form a premix, the premix dispersion time is 5-10 minutes, and after the dispersion is completed, dry the mixture to obtain a carbon black carrier;
[0024] Prepare a catalytic carrier; disperse a carbon black carrier and graphene oxide in a mixed solution formed by ethylene glycol and deionized water, and perform ultrasonic dispersion for 5-10 minutes; add acetic acid and γ-(2,3-epoxypropoxy)propyltrimethoxysilane and disperse for 15-20 minutes; after dispersion, add a hydrazine hydrate solution for mixing and dispersion, and adjust the pH to 8-9, and after mixing and dispersion, wash and dry to obtain a catalytic carrier;
[0025] Loading catalyst; the catalytic carrier is dispersed in a mixed solution of chloroplatinic acid solution and chloroauric acid solution, a surfactant is added in the dispersed state, and the dispersion time is 25min-30min; filtering treatment is performed after dispersion, and reduction treatment is performed after filtration to obtain a carbon-loaded Pt-Au bimetallic nanocatalyst.
[0026] In one of the embodiments, the step of preparing the carbon black carrier includes the following addition amounts, calculated by weight: 20-24 parts of carbon black, 38-42 parts of ethanol, 18-22 parts of deionized water, 8-12 parts of tetraethyl orthosilicate, 4-6 parts of epoxy soybean oil, and 2-4 parts of γ-aminopropyltriethoxysilane.
[0027] In one of the embodiments, the preparation of the catalyst carrier includes the following additions, calculated by weight: 26-30 parts of carbon black carrier, 4-6 parts of graphene oxide, 28-32 parts of ethylene glycol, 4-6 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 22-26 parts of deionized water, 2-3 parts of acetic acid, and 4-6 parts of hydrazine hydrate solution.
[0028] In one embodiment, in the catalyst loading step, the following addition amounts are included, calculated by weight: 28-32 parts of chloroplatinic acid solution, 28-32 parts of chloroauric acid solution, 4-6 parts of surfactant, and 33-37 parts of catalytic carrier.
[0029] In one embodiment, the carbon black is pre-treated by pickling and oxidation. The pickling is specifically dispersed in a 2mol / L hydrochloric acid solution, the addition amount is 150g-200g of carbon black per liter of hydrochloric acid solution, the dispersion time is 40min-50min, and after dispersion, it is filtered and washed with water until the pH of the filtrate reaches 6-7 and dried to obtain the acid-washed carbon black; the oxidation treatment is specifically ultrasonically dispersed in 1L hydrogen peroxide solution 20g-25g of carbon black after pickling, the ultrasonic dispersion time is 5min-10min, transferred to magnetic dispersion for 50min-60min, filtered and dried after dispersion.
[0030] In one embodiment, the drying process is specifically drying at 60° C.-70° C. for 20 min-30 min.
[0031] In one embodiment, the hydrazine hydrate solution is specifically a hydrazine hydrate solution with a mass fraction of 80%.
[0032] In one embodiment, the washing and drying treatment is specifically to use deionized water to wash for 1 min-2 min and then dry at 60° C.-70° C. for 30 min-40 min.
[0033] In one embodiment, the chloroplatinic acid solution is a chloroplatinic acid solution with a mass fraction of 1%; the chloroauric acid solution is a chloroauric acid solution with a mass fraction of 1%.
[0034] In one embodiment, the reduction treatment is specifically reduction by hydrogen, specifically reduction by introducing hydrogen at 110°C-140°C.
[0035] In one embodiment, the surfactant is specifically polydiallyldimethylammonium chloride.
[0036] In one embodiment, the pH adjustment is specifically to add ammonia water to adjust the pH.
[0037] In one embodiment, the hydrazine hydrate solution is specifically a hydrazine hydrate solution with a mass fraction of 80%, and its function is reduction.
[0038] In one embodiment, the adding of hydrazine hydrate solution for mixing and dispersing is specifically dispersing at 100° C. for 25 min-30 min.
[0039] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0040] The difference between Example 1-4 and Comparative Example 1-6 is that the preparation raw materials are different, and the preparation processes are the same, as shown in Table 1-3.
[0041] Table 1: Raw materials for the preparation of carbon black carrier
[0042]
[0043] Table 2: Raw materials for the preparation of catalytic carriers
[0044]
[0045] Table 3: Raw materials for the preparation of catalysts supported on catalytic carriers
[0046]
[0047] The chloroplatinic acid solution is specifically a chloroplatinic acid solution with a mass fraction of 1%; the chloroauric acid solution is a chloroauric acid solution with a mass fraction of 1%; the surfactant is specifically polydiallyldimethylammonium chloride; and the hydrazine hydrate solution is specifically a hydrazine hydrate solution with a mass fraction of 80%.
[0048] The preparation processes of Examples 1-4 and Comparative Examples 1-6 are as follows:
[0049] A method for preparing a carbon-supported Pt-Au bimetallic nanocatalyst, comprising the following preparation method:
[0050] Carbon black pretreatment;
[0051] The carbon black is pre-treated by pickling and oxidation. The pickling is specifically performed by dispersing the carbon black in a 2 mol / L hydrochloric acid solution, with an addition amount of 150 g of carbon black per liter of hydrochloric acid solution, and the dispersion time is 40 min. After the dispersion is completed, the carbon black is filtered and washed with water until the pH of the filtrate reaches 6-7 and then dried to obtain the pickled carbon black. The oxidation treatment is specifically performed by ultrasonically dispersing 20 g of the pickled carbon black in a 1 L hydrogen peroxide solution, with an ultrasonic dispersion time of 5 min, and then transferring to magnetic dispersion for 60 min. After the dispersion is completed, the carbon black is filtered and dried.
[0052] Prepare a carbon black carrier; disperse the carbon black in a mixed solution formed by ethanol and deionized water for 15 minutes; after the dispersion is completed, add ethyl orthosilicate dropwise for 30 minutes, and continue to disperse for 15 minutes after the addition is completed; add epoxy soybean oil and γ-aminopropyltriethoxysilane in sequence and disperse to form a premix, the premix is dispersed for 5 minutes, and after the dispersion is completed, it is dried at 60°C-70°C for 20 minutes-30 minutes to obtain a carbon black carrier;
[0053] A catalytic carrier is prepared; a carbon black carrier and graphene oxide are dispersed in a mixed solution of ethylene glycol and deionized water, and the ultrasonic dispersion time is 5 minutes; acetic acid and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are added and dispersed for 15 minutes; after the dispersion is completed, a hydrazine hydrate solution is added for mixing and dispersion, and the dispersion is carried out at 100° C. for 25 minutes to 30 minutes, and ammonia water is added to adjust the pH to 8-9, and after the mixing and dispersion is completed, the catalyst carrier is washed and dried to obtain the catalyst carrier; the washing and drying treatment is specifically washing with deionized water for 1 minute and then drying at 60° C. to 70° C. for 30 minutes.
[0054] Loading catalyst; the catalytic carrier is dispersed in a mixed solution of chloroplatinic acid solution and chloroauric acid solution, and a surfactant is added in the dispersed state, and the dispersion time is 25 minutes; after dispersion, filtering is performed, and after filtration, hydrogen is introduced at 110° C. for reduction treatment to obtain a carbon-loaded Pt-Au bimetallic nanocatalyst.
[0055] Comparative Example 7
[0056] The difference between Comparative Example 7 and Example 1 is that the carbon black is not pretreated in the preparation process, the amount of raw material added is the same, and other preparation processes are the same.
[0057] Relevant performance tests were conducted on Examples 1-4 and Comparative Examples 1-7, and the results are shown in Table 4. The catalytic activity is measured by the conversion rate of fuel oxygen, which is the conversion rate calculated by feeding the same amount of raw material under the same amount of platinum catalyst.
[0058] Table 4:
[0059]
[0060] It can be seen from the data in Table 4 that the carbon-supported Pt-Au bimetallic nanocatalysts prepared in Examples 1-4 have good overall catalytic efficiency, meet the operating requirements of fuel cells, and solve the technical problem of low overall catalytic efficiency of fuel cells in the prior art; specifically, the difference between Comparative Example 1 and Example 1 is that no carbon black carrier is added to the catalytic carrier of Comparative Example 1. It can be seen from the data in Table 4 that the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Comparative Example 1 is lower than the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Example 1. It can be seen that the addition of the carbon black carrier has a positive effect on the catalytic efficiency of the prepared carbon-supported Pt-Au bimetallic nanocatalyst. The addition of the carbon black carrier and the graphene oxide complement each other to form a distribution extending in all directions of space, so that it can be catalyzed on different spatial surfaces, thereby improving the overall catalytic efficiency.
[0061] The difference between Comparative Example 2 and Example 1 is that graphene oxide is not added to the catalytic carrier. It can be seen from the data in Table 4 that the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Comparative Example 2 is lower than the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Example 1. It can be seen that the addition of graphene oxide has a positive effect on the catalytic efficiency of the prepared carbon-supported Pt-Au bimetallic catalyst. The addition of graphene oxide and its use in combination with the carbon black carrier form a distribution extending in all directions of space, so that it can be catalyzed on different spatial surfaces, thereby improving the overall catalytic efficiency.
[0062] The difference between Comparative Example 3 and Example 1 is that tetraethyl orthosilicate is not added in the preparation of the carbon black carrier. It can be seen from the data in Table 4 that the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Comparative Example 3 is lower than that of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Example 1. It can be seen that the addition of tetraethyl orthosilicate to the carbon black carrier has a positive effect on the catalytic efficiency of the prepared carbon-supported Pt-Au bimetallic nanocatalyst. By adding tetraethyl orthosilicate, the surface of carbon black is partially coated with silica, which improves the degree of extension of the prepared catalytic carrier and improves the spatial distribution extension effect, thereby improving the overall catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst.
[0063] The difference between Comparative Example 4 and Example 1 is that no epoxidized soybean oil is added in the preparation of the carbon black carrier. It can be seen from the data in Table 4 that the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Comparative Example 4 is lower than that of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Example 1. It can be seen that the addition of epoxidized soybean oil to the carbon black carrier has a positive effect on the catalytic activity of the prepared carbon-supported Pt-Au bimetallic nanocatalyst. The addition of epoxidized soybean oil modifies the surface of carbon black, improves the degree of elongation, and increases the spatial contact area for loading Pt and Au, thereby improving the overall catalytic efficiency.
[0064] The difference between Comparative Example 5 and Example 1 is that γ-aminopropyltriethoxysilane is not added to the carbon black carrier in Comparative Example 5. It can be seen from the data in Table 4 that the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Comparative Example 5 is lower than that of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Example 1. It can be seen that the addition of γ-aminopropyltriethoxysilane to the carbon black carrier has a positive effect on the catalytic activity of the prepared carbon-supported Pt-Au bimetallic nanocatalyst. γ-aminopropyltriethoxysilane is added to treat the surface of carbon black, and amino groups are generated on the surface, which increases the degree of reaction with epoxidized soybean oil, thereby affecting the spatial extension of the carbon black carrier. When it is subsequently dispersed with graphene oxide, the dispersibility is improved, and the spatial extension of the catalytic carrier is improved, thereby improving the overall catalytic effect.
[0065] The difference between Comparative Example 6 and Example 1 is that γ-(2,3-epoxypropoxy)propyltrimethoxysilane is not added in the preparation of the catalytic carrier of Comparative Example 6. It can be seen from the data in Table 4 that the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Comparative Example 6 is lower than the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Example 1. It can be seen that the addition of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to the catalytic carrier has a positive effect on the catalytic activity of the prepared carbon-supported Pt-Au bimetallic nanocatalyst. The addition of γ-(2,3-epoxypropoxy)propyltrimethoxysilane improves the dispersibility of the mutual mixing of graphene oxide and the carbon black carrier, and the amino groups on the surface of carbon black extend to the surface of graphene oxide and react with the epoxy groups while reacting through γ-(2,3-epoxypropoxy)propyltrimethoxysilane, thereby improving the degree of reaction and the spatial extension, which positively affects the overall catalytic effect.
[0066] The difference between Comparative Example 7 and Example 1 is that in the preparation process of Comparative Example 7, the carbon black is not pretreated. It can be seen from the data in Table 4 that the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Comparative Example 7 is lower than the catalytic efficiency of the carbon-supported Pt-Au bimetallic nanocatalyst prepared in Example 1. It can be seen that pretreatment of carbon black has a positive effect on the catalytic activity of the prepared carbon-supported Pt-Au bimetallic nanocatalyst. The carbon black is pretreated to increase the specific surface area of the carbon black during the pickling process, and then the carbon black after pickling is oxidized to modify the surface of the carbon black, thereby increasing the degree of reaction with γ-aminopropyltriethoxysilane and epoxy soybean oil and increasing the spatial extension, thereby improving the overall catalytic efficiency of the fuel cell.
[0067] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0068] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a carbon-supported Pt-Au bimetallic nanocatalyst, characterized in that: It comprises the following preparation method, The carbon black is pre-treated by pickling and oxidation. Specifically, the pickling is to disperse the carbon black in a 2 mol / L hydrochloric acid solution, with an addition amount of 150 g to 200 g of carbon black per liter of hydrochloric acid solution, and the dispersion time is 40 min to 50 min. After the dispersion is completed, the carbon black is filtered and washed with water until the pH of the filtrate reaches 6 to 7, and then dried to obtain the pickled carbon black. Specifically, the oxidation treatment is to ultrasonically disperse 20 g to 25 g of the pickled carbon black in a 1 L hydrogen peroxide solution, and the ultrasonic dispersion time is 5 min to 10 min, and then transferred to magnetic dispersion for 50 min to 60 min. After the dispersion is completed, the carbon black is filtered and dried. Prepare a carbon black carrier; disperse the carbon black in a mixed solution formed by ethanol and deionized water for 10-15 minutes; after the dispersion is completed, add ethyl orthosilicate dropwise for 30-35 minutes, and continue to disperse for 10-15 minutes after the addition is completed; add epoxy soybean oil and γ-aminopropyl triethoxysilane in sequence and disperse to form a premix, the premix dispersion time is 5-10 minutes, and after the dispersion is completed, dry the mixture to obtain a carbon black carrier; Prepare a catalytic carrier; disperse a carbon black carrier and graphene oxide in a mixed solution formed by ethylene glycol and deionized water, and perform ultrasonic dispersion for 5-10 minutes; add acetic acid and γ-(2,3-epoxypropoxy)propyltrimethoxysilane and disperse for 15-20 minutes; after dispersion, add a hydrazine hydrate solution for mixing and dispersion, and adjust the pH to 8-9, and after mixing and dispersion, wash and dry to obtain a catalytic carrier; Loading catalyst; the catalytic carrier is dispersed in a mixed solution of chloroplatinic acid solution and chloroauric acid solution, a surfactant is added in the dispersed state, and the dispersion time is 25min-30min; filtering treatment is performed after dispersion, and reduction treatment is performed after filtration to obtain a carbon-loaded Pt-Au bimetallic nanocatalyst.
2. The method for preparing the carbon-supported Pt-Au bimetallic nanocatalyst according to claim 1, characterized in that: In the step of preparing the carbon black carrier, the following addition amounts are included, calculated by weight: 20-24 parts of carbon black, 38-42 parts of ethanol, 18-22 parts of deionized water, 8-12 parts of tetraethyl orthosilicate, 4-6 parts of epoxy soybean oil, and 2-4 parts of γ-aminopropyltriethoxysilane.
3. The method for preparing the carbon-supported Pt-Au bimetallic nanocatalyst according to claim 1, characterized in that: The catalyst carrier is prepared in the following amounts by weight: 26-30 parts of carbon black carrier, 4-6 parts of graphene oxide, 28-32 parts of ethylene glycol, 4-6 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 22-26 parts of deionized water, 2-3 parts of acetic acid, and 4-6 parts of hydrazine hydrate solution.
4. The method for preparing the carbon-supported Pt-Au bimetallic nanocatalyst according to claim 1, characterized in that: In the catalyst loading step, the following addition amounts are included, calculated by weight: 28-32 parts of chloroplatinic acid solution, 28-32 parts of chloroauric acid solution, 4-6 parts of surfactant, and 33-37 parts of catalyst carrier.
5. The method for preparing the carbon-supported Pt-Au bimetallic nanocatalyst according to claim 1, characterized in that: The drying process specifically comprises drying at 60° C.-70° C. for 20 min-30 min.
6. The method for preparing the carbon-supported Pt-Au bimetallic nanocatalyst according to claim 1, characterized in that: The hydrazine hydrate solution is specifically a hydrazine hydrate solution with a mass fraction of 80%.
7. The method for preparing the carbon-supported Pt-Au bimetallic nanocatalyst according to claim 1, characterized in that: The water washing and drying treatment specifically includes washing with deionized water for 1 min-2 min and then drying at 60° C.-70° C. for 30 min-40 min.
8. The method for preparing the carbon-supported Pt-Au bimetallic nanocatalyst according to claim 1, characterized in that: The chloroplatinic acid solution is specifically a chloroplatinic acid solution with a mass fraction of 1%; the chloroauric acid solution is a chloroauric acid solution with a mass fraction of 1%.
9. The method for preparing the carbon-supported Pt-Au bimetallic nanocatalyst according to claim 1, characterized in that: The reduction treatment is specifically carried out by reducing with hydrogen, and hydrogen is introduced at 110° C.-140° C. for reduction.
Citation Information
Patent Citations
Commercial antistatic and anti-wear polypropylene composite material and preparation method thereof
CN107383598A
Energy absorbing method based on dynamic polymer composition
CN109666164A